Factors influencing active and participatory learning of associate degree in nursing students in the classroom setting - Ly Chanvatanak; Sana, Erlyn A. (Manila The National Teacher Training Center for the Health Professions, University of the Philippines Manila, 2016)
A perennial complaint among teachers in Cambodia's Associate Degree in Nursing (ADN) deals with their students who do not participate actively during class discussions and activities. This study investigated the factors influencing active and participatory learning of ADN students. The study is a cross-sectional survey. A total of 247 from a total population of 689 students taking up the Associate Degree in Nursing (ADN) from year levels 1 to 3 of University of Health Sciences, Phnom Penh, Cambodia participated. Data collection procedure was done using a survey questionnaire on effective learning developed by (Bradshaw MJ & Lowenstein AJ 2007). An agreement scale was used with 1 representing strongly disagree, 2 disagree, 3 agree, and 4 strongly agree. Classroom observations and separate focus group discussions between selected teachers and students from all year levels and different areas were also done. Scores in the scale were analyzed using means and qualitative data were content analyzed. Out of 247 respondents, 105 (42.5%) were males and 142 (57.5%) females. There were 99 respondents (40.1%) from the first year, 64 (25.9%) from second year, 84 (34%) from third year. The youngest was 16 years old, the oldest was 23, and the mean age was 20. Students? mean rating on processes engaged by students before daily classroom discussion was only 3.03; those they actively engaged in during classes registered an overall mean of 3.00. Teacher strategies reported as contributory to active and participatory learning were use of small group, up-to-date ICT, awards, interactive classroom environments. The groups of students who came from the city (mean=3.01)and from provinces (mean=3.01) were compared. The t-test and p value obtained suggested that there was no significant difference between participatory learning of students from both origins. The ADN students were passive learners and the classroom managed by teachers who supervised all activities. Interactive teaching strategies used by their teachers such as role playing, small group discussions, up-to-date technology as teaching didactic and friendly approach were encouraging them to participate in active learning. There were no significant differences between students from Phnom Penh and the Province in their daily classroom participation. Teachers play an important role in encouraging active participation during classroom discussions. Class schedule, student?s assessment methods, evaluation tools should be changed as needed. Academic awards should be officially announced and given regularly. The use of ICT as teaching strategy is also recommended. Future studies of nurse teachers from additional colleges, both public and private should be encouraged to involve researchers to determine if the findings would be similar in order to bring about active and participatory to the entire nursing education system in Cambodia.
Thesis (Master of Health Professions Education)--University of the Philippines Manila, May 2016
Panel members: /Adviser; Melflor A. Atienza MD MHPED, Reader/Critic; Chhay Seak Chap MD MPH MHPED, Member; Team Sar RMT MBA MHPED, Member
Keywords: Nursing -- Study and teaching; Learning strategies